2021
DOI: 10.1126/sciadv.abf8755
|View full text |Cite
|
Sign up to set email alerts
|

Multidecadal poleward shift of the southern boundary of the Antarctic Circumpolar Current off East Antarctica

Abstract: The southern boundary (SB) of the Antarctic Circumpolar Current, the southernmost extent of the upper overturning circulation, regulates the Antarctic thermal conditions. The SB’s behavior remains unconstrained because it does not have a clear surface signature. Revisited hydrographic data from off East Antarctica indicate full-depth warming from 1996 to 2019, concurrent with an extensive poleward shift of the SB subsurface isotherms (>50 km), which is most prominent at 120°E off the Sabrina Coast. The SB s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 46 publications
(130 reference statements)
3
36
0
Order By: Relevance
“…2a). This temperature change is broadly in line with those estimated previously in the same region 7,15,16 and, remarkably, it is concurrent to an even more pronounced warming of 0.8-2ºC (or 0.1-0.4ºC per decade) over the continental slope (Fig. 1).…”
Section: Deep Warming Off East Antarcticasupporting
confidence: 91%
See 2 more Smart Citations
“…2a). This temperature change is broadly in line with those estimated previously in the same region 7,15,16 and, remarkably, it is concurrent to an even more pronounced warming of 0.8-2ºC (or 0.1-0.4ºC per decade) over the continental slope (Fig. 1).…”
Section: Deep Warming Off East Antarcticasupporting
confidence: 91%
“…Our focus on the Indian Ocean sector stems from this region's glaciers contributing the bulk of East Antarctic ice-mass loss in recent decades 9,17,18 . Our evaluation of long-term water-mass variability off East Antarctica presents two important advances relative to previous studies 15,16 , in that our dataset: (i) has a substantially improved spatial coverage of the seasonally ice-covered areas near the East Antarctic margins, particularly over the continental slope and shelves; and (ii) spans a longer (by several decades) period.…”
Section: Deep Warming Off East Antarcticamentioning
confidence: 99%
See 1 more Smart Citation
“…One of the factors that may cause variations of xCO 2 sea is the spatial distribution of front positions. The discovery by Yamazaki et al (2021) that the Southern Boundary (SB) of Antarctic Circumpolar Current (ACC) moved southward during the period between BROKE and this study indicates that the upwelling region of Circumpolar Deep Water (CDW) moved southward. As a result, the maximum concentration of nitrate near the TML increased, and the difference in nitrate concentrations between the ocean surface and the TML increased (Figure 13).…”
Section: Decadal Trendmentioning
confidence: 68%
“…Significant changes have taken place in the marine environment of the Indian sector during the two decades since the BROKE study (Auger et al, 2021). For example, Yamazaki et al (2021) have shown that the Southern Boundary (SB) of the Antarctic Circumpolar Current (ACC) moved southward from 1996 to 2019. This caused changes in the distribution of nutrients and might influence the seasonal variability of pCO 2 .…”
mentioning
confidence: 99%